Existence and uniqueness of mild solutions of second order semilinear differential equations in Banach space - Gorbatenko, Ya. V. (Methods of Functional Analysis and Topology, 2011)
We consider the Cauchy problem for second order semilinear differential equations in Banach space. Sufficient conditions of local and global existence and uniqueness of mild solutions are presented.